Perfusion mapping with Tc-HMPAO in cerebral haematomas. Issue 12 (December 1991) - Rousseaux, M; Steinling, M; Huglo, D; Mazingue, A; Barbaste, P
Abstract : The cerebral distribution of HMPAO was mapped tomographically by SPECT in 20 patients with an intra cerebral haematoma. The images were assessed visually and by an analysis of an asymmetry index (AI) for various cerebral areas. Visual inspection identified the lesion in each of the 20 cases. Reduced tracer activity and abnormal AI were consistent findings. Remote effects (diaschisis) were also observed in the adjacent (19 cases) and frontal (14 cases) cortex, and in the controlateral cerebellum (16 cases). Sequential studies at 60, 150 and 300 minutes in 10 patients showed remarkably stable patterns. HMPAO maps were compared with cerebral blood flow (CBF) measured with 133 Xenon (133Xe) in eight cases. The two methods showed similar results in the region of a lesion, but remote effects were more obvious with the 133Xe in two patients.